DANCE LIKE THE CONTENT OF PHYSICAL EDUCATION IN CARDIOVASCULAR DISEASE PREVENTION. (Fiep Bulletin - online, 2017)
Aims: The tumultuous life and routines lived in search of survival, it has made men and women fail to take care of yourhealth. Evidence shows that physical inactivity and sedentary condition pose a serious deterioration of normal bodily functions,especially when linked to other risk factors for chronic degenerative diseases and, consequently, to the emergence ofcardiovascular disease. The exercise program of aerobic predominance condition the cardiovascular system providing positivechanges in relation to chronic degenerative disorders and the dance becomes an option, opening the way for a new conception oflife, where all people regardless of their age, can express their feelings and emotions through the rhythmic body movement.Methodology: Literature review by subject in MEDLINE (PUBMED), BIREME (LILACS) and SCIELO database, published from2009 to 2014 and books published from 1973 to 2010. Objective: evidence about the importance of content as a dance exercisemodality, its physical benefits and organic as the aerobic fitness in the prevention of chronic degenerative diseases andcardiovascular diseases. Conclusions: It follows that dance when practiced respecting the principles of continuous movement,long-term, moderate light intensity, provides a perfect balance of state "Steady State" between the consumption and supply ofoxygen in the body. For this activity to be controlled more effectively, calculations from the maximum heart rate, obtaining reliableresults of the target zone training, ensure the practitioners physical and organic benefits that dance can provide.